2017
DOI: 10.1007/s00128-017-2066-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Thiophanate Methyl and Propiconazole in Grape and Mango Fruits Under the Egyptian Field Conditions

Abstract: This research aims at determining residues of thiophanate methyl and propiconazole in grape and mango fruits as an indication for their persistence in this environmental compartment. Fruit extracts were analyzed for thiophanate methyl using High Performance Liquid Chromatography and using Gas Chromatography Electron Capture Detector (GC/ECD), respectively. The results indicated that propiconazole had a less environmental impact since propiconazole had shorter residue half-lives which were 1.24 and 1.19 days in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The rank of DT 50 for three tests was July > August > June. There have been DT 50 values reported for TM in biological samples, such as 1.52 days in tea (Chen et al, ), 2.49 days in mango (Soliman et al, ), 2.64–7.00 days in grape (Dong, Zeng, & Bai, ; Mandal, Das, & Bhattacharyya, ; Soliman et al, ) and 22–41 days in carnation leaf (Brouwer, De Haan, Leenheers, De Vreede, & Van Hemmen, ), depending on the plants, culture conditions and even fitting models (Fantke & Juraske, ). The comparison of DT 50 values indicated that the dissipation of TM in apple leaves was slower than that in tea or mango, approximately equal to that in grape and faster than that in carnation leaf.…”
Section: Resultsmentioning
confidence: 99%
“…The rank of DT 50 for three tests was July > August > June. There have been DT 50 values reported for TM in biological samples, such as 1.52 days in tea (Chen et al, ), 2.49 days in mango (Soliman et al, ), 2.64–7.00 days in grape (Dong, Zeng, & Bai, ; Mandal, Das, & Bhattacharyya, ; Soliman et al, ) and 22–41 days in carnation leaf (Brouwer, De Haan, Leenheers, De Vreede, & Van Hemmen, ), depending on the plants, culture conditions and even fitting models (Fantke & Juraske, ). The comparison of DT 50 values indicated that the dissipation of TM in apple leaves was slower than that in tea or mango, approximately equal to that in grape and faster than that in carnation leaf.…”
Section: Resultsmentioning
confidence: 99%
“…The pesticide offers the benefits of protection, treatment, and absorption and can prevent the growth and reproduction of fungi by interfering with ergosterol biosynthesis and inhibiting steroid demethylation 9 . It is widely used to control fungal diseases, such as alternaria black spot, anthracnose, grey mould, and powdery mildew, on fruits, vegetables, cereals, and other field crops 6,8,10,11 . The fungicide is usually sprayed twice to control leaf spot on celery and three times to control violet leaf spot on onion.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous literature, a number of studies on the residual behaviour of propiconazole in banana, grape, mango, pomegranate, wheat, and ginseng domestically and internationally have been reported 6–8,10–12 . However, there has been no systematic study conducted on degradation behaviour, residue distribution, and dietary risk assessment of propiconazole in celery and onion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Quick Easy Cheap Effective Rugged Safe (QuEChERS) method, in combination with LC-MS/MS has gained considerable attention for the sensitivity level they attain, beside the good selectivity and short analysis time (Akkbik and Hazer 2018;Chen et al 2013;Dong et al 2018;Economou et al 2009;Ferreira et al 2016;Qin 2016;Wu et al 2015;Yu et al 2017;Zhang et al 2012). On the other hand, solid phase extraction (SPE) methods have been frequently applied in combination with HPLC-DAD (Chen et al 2015;Soliman et al 2017;Veneziano et al 2004;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%